Public Service Model on Bureaucracy Reform in Lampung Utara - Irhammudin Irhammudin; M. Ruhly Kesuma Dinata (Constitutionale, 2022)
This study aims to identify the implementation of bureaucratic reform and offer several solutions for improving licensing administration services. This research uses a qualitative approach with the type of instrumental case study research. The research was carried out at the North Lampung Regency Licensing Service. Data collection techniques were used: in-depth interviews, document studies and observation. The results showed that the implementation of bureaucratic reform in licensing administration services, from the institutional aspect to the licensing service for North Lampung Regency, was a Stop Service. Aspects of Human Resources show that the qualifications of existing employees are not following the organization's needs, as well as the fact that discipline and responsibility of employees are still relatively low. Regional governance reform begins with the form of regional autonomy. Regional autonomy represents the authority to regulate government businesses that have a local character following initiatives that follow the community's aspirations. Regional governance reform aims to maximize service functions with a more public locality character. Reform of the implementation of regional governance can be carried out by relating to the conception of a new public service oriented towards community services that are responsive to various public values ​​and interests and are also non-discriminatory.